Integrating travel behavior with land use regression to estimate dynamic air pollution exposure in Hong Kong. (April 2018) - Tang, Robert; Tian, Linwei; Thach, Thuan-Quoc; Tsui, Tsz Him; Brauer, Michael; Lee, Martha; Allen, Ryan; Yuchi, Weiran; Lai, Poh-Chin; Wong, Paulina; Barratt, Benjamin
Abstract: Background: Epidemiological studies typically use subjects' residential address to estimate individuals' air pollution exposure. However, in reality this exposure is rarely static as people move from home to work/study locations and commute during the day. Integrating mobility and time-activity data may reduce errors and biases, thereby improving estimates of health risks. Objectives: To incorporate land use regression with movement and building infiltration data to estimate time-weighted air pollution exposures stratified by age, sex, and employment status for population subgroups in Hong Kong. Methods: A large population-representative survey (N = 89, 385) was used to characterize travel behavior, and derive time-activity pattern for each subject. Infiltration factors calculated from indoor/outdoor monitoring campaigns were used to estimate micro-environmental concentrations. We evaluated dynamic and static (residential location-only) exposures in a staged modeling approach to quantify effects of each component. Results: Higher levels of exposures were found for working adults and students due to increased mobility. Compared to subjects aged 65 or older, exposures to PM2.5, BC, and NO2 were 13%, 39% and 14% higher, respectively for subjects aged below 18, and 3%, 18% and 11% higher, respectively for working adults. Exposures of females were approximately 4% lower than those of males. Dynamic exposures were around 20% lower than ambient exposures at residential addresses. Conclusions: The incorporation of infiltration and mobility increased heterogeneity in population exposure and allowed identification of highly exposed groups. The use of ambient concentrations may lead to exposure misclassification which introduces bias, resulting in lower effect estimates than 'true' exposures. Graphical abstract: Unlabelled Image Highlights: The use of ambient concentration may not accurately represent air pollution exposure. 'Static' estimates do not account for time spent in indoor microenvironments. Time-activity and related exposure differ dramatically across population groups. Travel survey can be used to derive population mobility and 'dynamic' exposure. Integrating mobility avoids exposure misclassification, reducing biases in analyses.